2019
DOI: 10.1167/19.4.24
|View full text |Cite
|
Sign up to set email alerts
|

Visual shape perception in the case of transparent objects

Abstract: In order to estimate the shape of objects, the visual system must refer to shape-related regularities in the (retinal) image. For opaque objects, many such regularities have already been identified, but most of them cannot simply be transferred to transparent objects, because they are not available there at all or are available only in a substantially modified form. We here consider three potentially relevant regularities specific to transparent objects: optical background distortions due to refraction, change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Why might purely refractive objects be perceived flatter than the objects with other material properties? It is known that the surface slant of transparent objects tends to be underestimated, and the result depends on a combination of transparent object properties and the surrounding environment ( Schlüter & Faul, 2019 ). It is possible that other sources of information may be relevant (e.g., Shape from texture).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why might purely refractive objects be perceived flatter than the objects with other material properties? It is known that the surface slant of transparent objects tends to be underestimated, and the result depends on a combination of transparent object properties and the surrounding environment ( Schlüter & Faul, 2019 ). It is possible that other sources of information may be relevant (e.g., Shape from texture).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than observers matching internal experiences of refractivity, these researchers found that observers tended to match surfaces directly based on similarity in image cues: specular reflections and the distortion field. Further studies have used gauge figure tasks to estimate variations in perceived surface slant (i.e., surface curvature) and found that the 3D shape of objects with semiopaque reflectance properties tends to be perceptually underestimated ( Chowdhury et al., 2017 ; Schlüter & Faul, 2019 ). These interactions between perceived shape and material properties suggest that the perception of both shape and materials depends on similar sources of image-based information.…”
mentioning
confidence: 99%
“…At the boundary of the media, the difference between their refractive indices defines the angle the light ray is refracted with. Therefore, the refractive index has a strong impact on the background distortion in see-through images (proposedly also contributing to shape perception Schlüter & Faul, 2019). Fleming et al (2011) have shown that humans are surprisingly good at estimating refractive indices of transparent materials, proposedly relying on a background distortion cue (although subject to biases owing to the object's thickness and distance to the background).…”
Section: Index Of Refractionmentioning
confidence: 99%
“…Regardless of these attempts, the role of the refractive index in the appearance of non-see-through materials remains understudied. Additionally, difference in the refractive indices of the two bounding media modulates the magnitude of the Fresnel reflection and transmission, more refractive objects usually appearing glossier (Fleming et al, 2011;Schlüter & Faul, 2019) (also impacting caustics; Kán & Kaufmann, 2012;Lynch et al, 2001). This is illustrated in Figure 7.…”
Section: Index Of Refractionmentioning
confidence: 99%
“…Material perception is a complex process that involves a large number of distinct dimensions (Mao et al, 2019;Obein et al, 2004;Sève, 1993) that, sometimes, are impossible to physically measure (Hunter et al, 1937). The illumination of a scene (Beck & Prazdny, 1981;Bousseau et al, 2011;Zhang et al, 2015) and the shape of a surface, are responsible for the final appearance of an object (Nishida & Shinya, 1998;Schlüter & Faul, 2019;Vangorp et al, 2007) and, therefore, for our perception of the materials it is made of (Olkkonen & Brainard, 2011). Humans are capable of estimating the reflectance properties of a surface (Dror et al, 2001b) even when there is no information about its illumination (Dror et al, 2001a;Fleming et al, 2001), yet we perform better under illuminations that match real-world statistics (Fleming et al, 2003).…”
Section: Interplay Of Geometry and Illuminationmentioning
confidence: 99%